Ultrasound-Assisted Hydrothermal Synthesis of SrSnO3/g-C3N4 Heterojunction with Enhanced Photocatalytic Performance for Ciprofloxacin under Visible Light - Zhengru Zhu; Haiwen Xia; Junchao Jiang; Songlin Han; Hong Li (Crystals, 2022)
In this work, an SrSnO3/g-C3N4 heterojunction with different dosage of SrSnO3 was fabricated by an ultrasound-assisted hydrothermal approach and characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-visible diffuse reflectance spectra (UV-Vis DRS), and photoluminescence spectroscopy (PL). Ciprofloxacin was adopted to assess the degradation performance, and the sample combined with 40% SrSnO3 eliminated 93% of ciprofloxacin (20 mg/L) within 3 h under visible light, which is 6.6 and 1.7 times greater than for SrSnO3 and g-C3N4, respectively. Furthermore, 85% CIP was extinguished after five cycles of a photocatalytic process. Ultimately, a possible photocatalytic mechanism was dissected.